Modeling the heterogeneous catalytic recovery processes of aldehydes and ketones - Skoretska, Ivanna; Beznosyk, Yuri (Eastern-European Journal of Enterprise Technologies, 2017)
Mathematical models of the recovery reactions of cyclohexanone and anise aldehyde with subsequent esterification by the Meerwein-Ponndorf-Verley mechanism are constructed. Experimental research was conducted into recovery reactions of aldehydes and ketones in order to find the optimal catalyst for the recovery reaction of cyclohexanone and to establish the limiting stage in the recovery process of anise aldehyde. We analyzed the activity of three catalysts, in the presence of which the recovery reaction of cyclohexanone proceeded, and selected for further calculations and studies the most active zeolite – SnMgAl(СО3). By using the MathCad 15.0 programming environment, we solved the inverse problem of chemical kinetics for the examined reactions. It was found that the value of rate constant of the recovery reaction of cyclohexanone in the presence of zeolite SnMgAl(СО3) is the largest and reaches 0.2544 s-1, in other words, this is the most effective catalyst. As far as the recovery reaction of aldehyde anise is concerned, it was established that the first stage of this reaction (anise aldehyde recovery) proceeds slower than the second stage (anise alcohol esterification) and it is the limiting stage of the reaction. Results obtained in the course of experimental research might be used to solve the direct and inverse problems of chemical kinetics.